Influencia del ph y el tiempo en la adsorción de Ca2+ y Mg2+ con cenizas volantes de la industria azucarera - Galvez Cubas, Johnny Lorenz (2018)
The purpose of this research was to determine the influence of pH and the contac time in the adsorption of alkaline ions earthy Ca+2 and Mg+2 of natural groundwater using fly ash, a waste of the sugar industry that generates pollution in the environment. The initial concentrations of the water to be treated were 227.90 mg Ca+2/L and 61.90 mg Mg+2/L; the adsorption treatment consisted of putting natural groundwater in contact with the ash using a magnetic stirrer. In the pH range and contact time studied was achieved the greatest adsorption of ions at a pH of 9 and 3 hours, reaching the concentration of 168.37 mg Ca+2/L representing 73.88 % of total Ca+2, and the proportion of water with ash is 20 grams of fly ash/litre of groundwater. The results see a direct relationship of pH and contact time in the adsorption of Ca+2 ions; Mg+2 ions are not adsorbed under the investigated parameters. The determination of Ca+2 and Mg+2 ions was performed by the method of Complexometry using volumetric titration with EDTA, using EBT and murexide as indicators